Peningkatan Stabilitas Lereng pada Ruas Jalan Tawaeli – Toboli dengan Vegetasi/Bioengineering - Wandira, S.A.; Rahayu, A. (Civil Engineering Department, Tadulako University, 2021)
Tawaeli - Toboli is one of the road that often undergo landslide. Most of these roads are in a mountainous area with high steep slopes and poor soil conditions. The road conditions worsened, especially in rainy season resulting the citizen do not know anywhere that is prone to landslides such as in Km 16 to 17. The purpose of this study was to analyze slope stability using bioengineering methods, determine the shear strength of soil without plant roots and soil with plant roots and to determine the potential for landslides that will occur. Bioengineering is used to increase the strength of the soil, and stabilize slopes and reduce erosion on slopes. The slope stability calculation using the Bishop slice method. The calculating of safety factor analyzed using the Slope / W application and manually. Soil samples were taken from 3 (three) points and the soil strength parameters, soil cohesion and friction angle, were obtained through laboratory testing. Tests were carried out using rootless and rooted soil samples. In addition, direct field observations were made to obtain slope angles and slope heights. The results showed that the parameters of soil shear strength, cohesion and friction angle increased with the presence of plant roots. The results of the slope stability analysis show that the conditions of the slope are stable at slope 1 (Km 16) and slope 3 (Km 17) with a safety factor greater than 1.5. While slope 2 (Km 16 +300) has the potential for landslides as a safety factor of less than 1.5. The use of bioengineering increases the safety factor to be greater than 1.5. The calculation of the value of the safety factor using the Slope / W program and the Bishop manual is not much different, but the calculation time with the Slope / W program is faster